The effects of acute hypoxia and hypercapnia on oxygen consumption of the freshwater European eel - Cruz-Neto, A. P. [UNESP]; Steffensen, J. F. (My University, 1997)
When exposed to hypoxia, eels Anguilla anguilla were able to regulate and maintain VO2 down to a water oxygen tension (PWO2) of about 25 mmHg, a value far below those reported in other studies. When exposed to hypercapnia, eels showed a depression in VO2 as water carbon dioxide tension (PWCO2) increased. Faced with combined hypoxia-hypercapnia, eels showed an increase in their sensitivity to hypoxia, and the critical oxygen tension increased to 40-45 mmHg. The possible mechanisms underlying these responses were discussed, and the implications of such findings for extensive culture of eels were highlighted.
Keywords: Anguilla anguilla; aquaculture; European freshwater eel; hypercapnia; hypoxia; oxygen consumption